Supermercantilism as a European strategy: The road to stagnation - Wolfgang Hager (Intereconomics, 1984)
On the surface, Europe seems to be climbing out of the dreary post-1973 era, marked by anxiety, doubts, and shocks, to a new “1960s”: economic growth, declining inflation, new consumer gadgets to enjoy. But the medium-term outlook is more disturbing than the euphoria engendered by a temporary economic upswing would suggest. While the general introduction of technologies matured in past decades seems to usher in a new era of creativeness in our economies, the overall economic policy context, expressly designed to foster such creativeness, bears the seeds of profound disequilibria.
Keywords: 330; EC